A chromosome-level genome assembly for Onobrychis viciifolia reveals gene copy number gain underlying enhanced proanthocyanidin biosynthesis - Junyi He; Danyang Tian; Xue Li; Xuemeng Wang; Tingting Wang; Ziyao Wang; Hui Zang; Xiaofan He; Tiejun Zhang; Quanzheng Yun; Rengang Zhang; Jishan Jiang; et al. (Communications Biology, 2024)
Abstract Sainfoin (Onobrychis viciifolia), which belongs to subfamily Papilionoideae of Leguminosae, is a vital perennial forage known as “holy hay” due to its high contents of crude proteins and proanthocyanidins (PAs, also called condensed tannins) that have various pharmacological properties in animal feed, such as alleviating rumen tympanic disease in ruminants. In this study, we select an autotetraploid common sainfoin (2n = 4x = 28) and report its high-quality chromosome-level genome assembly with 28 pseudochromosomes and four haplotypes (~1950.14 Mb, contig N50 = 10.91 Mb). The copy numbers of genes involved in PA biosynthesis in sainfoin are significantly greater than those in four selected Fabales species, namely, autotetraploid Medicago sativa and three other diploid species, Lotus japonicus, Medicago truncatula, and Glycine max. Furthermore, gene expansion is confirmed to be the key contributor to the increased expression of these genes and subsequent PA enhancement in sainfoin. Transcriptomic analyses reveal that the expression of genes involved in the PA biosynthesis pathway is significantly increased in the lines with high PA content compared to the lines with medium and low PA content. The sainfoin genome assembly will improve our understanding of leguminous genome evolution and biosynthesis of secondary metabolites in sainfoin.